Dependencia de dispositivos celulares y calidad del sueño en estudiantes de Psicología Clínica de la Universidad Nacional de Loja, 2022 - 2023 - Betancourt Rivas, Kelvin Alexander (2023)
Currently, the use of cellular devices has caused a great impact on the activities of human beings and in all social groups due to the progressive advances that this technological tool maintains, where its use fluctuates between the acquisition of knowledge and leisure activities; however, its problematic and disproportionate use could generate certain dependence, which is characterized by the loss of control and intense desire to continue using the device despite the consequences it generates with the purpose of achieving immediate satisfaction or pleasure. With this background, the present research aims to establish the relationship between dependence on cellular devices and sleep quality in students of Clinical Psychology at the National University of Loja. The research had a quantitative approach of descriptive and correlational type, conducted with 121 students. The psychometric instruments applied were the Mobile Dependence Test (TDM) and the Pittsburg Sleep Quality Index (PSQI), determining that the level of dependence on cellular devices is at three levels; 15.7 % at a low level, 47.1 % at a moderate level and 37.2 % at a high level. Similarly, the quality of sleep was evidenced; where 51.2 % maintain a poor quality of sleep as opposed to 48.8 % who maintain a good quality of sleep. Therefore, the data obtained and subjected to the corresponding statistical analysis, established that there is no statistically significant correlation between dependence on cellular devices and sleep quality